Addiction veridiction: gendering agency in legal mobilisations of addiction discourse - Seear, K.; Fraser, Suzanne (2016)
This paper explores the question of whether and in what ways the law and legal processes work to stabilise addiction as a health problem or ‘disease’. In undertaking this analysis, we also explore the associated gender implications of these practices and the means through which legal processes that stabilise addiction simultaneously stabilise gender. Using the work of science and technologies scholar Bruno Latour, in particular his anthropological analysis of scientific and legal ‘modes of existence’, we explore legal processes of what he calls ‘veridiction’ – or the specific processes by which law distinguishes truth from falsity – associated with addiction. We focus on processes that are largely hidden from public view and as such receive little scrutiny, but through which the meaning of addiction as a disease is secured. Our aim is to consider the role of legal negotiations in establishing agreed facts, and to explore lawyers’ understanding of these processes. We argue that although in public discourse judges are ascribed the status of the law’s key decision-making figures, lawyers’ accounts do not necessarily support this view. Instead, their accounts of the judicial process foreground their own and other lawyers’ role in decisions about addiction, despite an absence of training or education in the area. We also note that lawyers’ accounts suggest little independent oversight – even from judges – of the work lawyers do in stabilising addiction ‘facts’. Based on these observations, we consider the ways such processes of stabilisation impact on women in the legal system whose lives are in some way affected by discourses of addiction as a disease. We argue that legal practices of veridiction are centrally implicated in the making of both gender and health and that elements of these processes, which are not often publicly visible or subjected to scrutiny, require more analysis.